Islamic scholars’ perspectives on wives as primary breadwinners during the COVID-19 pandemic - Ahdiyatul Hidayah; Nurul Huda (An-Nisa’ Journal of Gender Studies, 2023)
The COVID-19 pandemic disrupted family economies and affected households’ ability to meet daily needs. This study aims to analyze Muslim scholars’ perspectives on wives serving as primary breadwinners during the COVID-19 pandemic and to identify the factors contributing to this shift in roles. This study employed a literature-based research method with a descriptive qualitative approach. Data were collected through documentation and analyzed using thematic analysis, with validation through source triangulation, reference adequacy, and peer debriefing. The findings reveal two main points. First, Muslim scholars position financial maintenance (nafaqah) as primarily the husband’s responsibility, while wives may assume the role of primary breadwinner under particular circumstances, including husbands’ incapacity, illness, death, abandonment, or economic hardship. Second, four factors contributed to wives becoming primary breadwinners during the pandemic: economic pressure, husbands’ neglect of maintenance obligations, limited fulfillment of family responsibilities, and husbands’ inability to work due to illness. The study concludes that the pandemic accelerated changes in wives’ economic roles while their domestic responsibilities often remained, creating a double burden. The study contributes to role theory by demonstrating that role transformation may emerge as an adaptive response to crises and household vulnerabilities. It also highlights the importance of Islamic family law literacy, community-based marital counseling, and mechanisms for protecting wives’ economic rights.